Avaliação esportiva utilizando técnicas multivariadas: construção de indicadores e sistemas online - Maiorano, Alexandre Cristovão (2014)
The main objective of this research is to provide statistical tools that allow the comparison of individuals in a speci ed sports category. Particularly, the present study is focused on the performance evaluation in football using univariate and multivariate methods. The univariate approach is given by Z-CELAFISCS methodology, which was developed with the purpose of identifying talents in the sport. The multivariate approaches are given by the construction of indicators, speci cally by means of principal component analysis, factor analysis and copulas. These indicators allows the reduction of the dimensionality of the data in studying, providing better interpretation of the results and improving comparability between the performance and assortment of individuals. To facilitate the use of the methodology studied here was built an online statistical system called i-Sports.